The credibility of Hong Kong's currency board system: Looking through the prism of MS-VAR models with time-varying transition probabilities - Boris Blagov; Michael Funke (Bank of Finland, Institute for Economies in Transition (BOFIT), 2014)
​This paper takes seriously the idea that the coefficients of a VAR and the variance of shocks may be time-varying and so employs a Markov regime-switching VAR model to describe and analyse the time-varying credibility of Hong Kong's currency board system. The endogenously estimated discrete regime shifts are made dependent on macroeconomic fundamentals. This enables us to determine which changes in macroeconomic variables can trigger switches between the low and high credibility regimes. We carry out extensive testing to search for the most appropriate specification of the Markov regime-switching model. We find strong evidence of regime switching behaviour that portrays the timevarying nature of credibility in the historical data. Our own conditional volatility index provides anticipatory signals and amplifies the regime-switching transition probabilities. Publication
URN:NBN:fi:bof-201411073145
Keywords: C11; C32; F31; F41; 330; Markov regime-switching VAR; exchange rate regime credibility; Hong Kong